EVALUATION OF GST’S IMPACT ON SMALL AND MARGINAL FARMERS IN HARDA DISTRICT - Patel, Rohit; Sahu, Jaikishan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Goods and Services Tax (GST) in India, a unified indirect taxation system, has affected agriculture and other sectors. This article examines how GST impacts small and marginal farmers in Harda District, Madhya Pradesh, by examining their post-GST benefits and drawbacks. We examine changes in agricultural market access, input costs, and tax structure. This article stresses the financial burden farmers face from GST compliance, its effects on input costs, and its effects on agricultural product pricing using surveys, interviews, and secondary data analysis. The study also assesses GST exemptions and subsidies for farmers and suggests policy adjustments to mitigate their detrimental effects on this sensitive rural sector. The results aim to comprehend small and marginal farmers’ financial situation under the new tax structure and recommend solutions to boost their agricultural participation.